Eel Oil Attenuates Acetaminophen-Induced Acute Liver Injury Through Inhibition of Oxidative Stress in Rats - Heru Sasongko; Renita Wahyu Nur Hidayati; Bayu Anggoro Saputro; Muhammad Fiqri Zulpadly Mahmud; Yeni Farida (Majalah Obat Tradisional, 2023)
Health practitioners all over the world have studied liver injury caused by drug side effects. Excessive production of free radicals causes cell damage, which has implications for pathological conditions in both humans and animals. Omega-3 fatty acids are a component of fish that can work as hepatoprotective agents. Eel (Anguilla bicolor) is known to contain omega-3 including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). This study aimed to evaluate the hepatoprotective activity of eel oil on rats via inhibiting oxidative stress. Methods: Acetaminophen-induced male Wistar rats were used as liver injury experimental models. Rats were divided into 5 groups, namely normal control, negative control, positive control (silymarin, 100 mg/kg), and two groups of eel oil dose (2000 mg/kg and 4000 mg/kg). The study was conducted for 14 days. The levels of serum glutamic pyruvic transaminase (SGPT), serum glutamic pyruvic transaminase (SGOT), alkaline phosphatase (ALP), total bilirubin, albumin, Malondialdehyde (MDA), and glutathione (GSH) levels of the liver organ were measured. The data were analyzed using statistics and analysis of variance. Results: The study showed that eel fish oil can reduce SGPT and total bilirubin levels of male Wistar rats induced by acetaminophen. Eel oil at a dose of 4000 mg/kg could significantly reduce SGPT and liver bilirubin levels in male Wistar rats (p<0.05). Eel oil is effective in reducing malondialdehyde (MDA) levels and increasing glutathione (GSH) levels at a dose of 2000 mg/kg. Conclusion: Eel oil has hepatoprotective activity by inhibiting SGPT, total bilirubin, MDA, and increasing GSH levels in rats.